Economic growth in Georgia: Historical perspectives and prognosis - Alexander Milnikov; Tatiana Papiashvili; Irakli Rodonaia (IBSU Scientific Journal (IBSUSJ), 2008)
While output declined in virtually all transition economies in the initial years, the speed and extent of the recovery that followed had varied widely across the transition countries. The paper examines some aspects of transition experiences of 1990s and the dynamics of GDP in Georgia during transition recession and following post-recession recovery. GDP prognostic econometric model for Georgia is developed.
Keywords: 330; economic growth; GDP; transitional economy; prognostic model; non-linear trend